Cyclonic storms and Depressions over the north Indian Ocean during 2019* - A, Kashyapi; V K, Shripad; J C, Natu (MAUSAM, 2020)
During 2019, in all 12 intense low pressure systems formed over the Indian Seas. These include; one Super cyclonic storm (KYARR), one extremely severe cyclonic storm (FANI), 4 very Severe Cyclonic Storms (VAYU, HIKAA, MAHA & BULBUL), 2 Cyclonic Storms (PABUK & PAWAN), 3 Deep Depressions and 1 Depression. Out of these 12 systems, 4 systems formed over the Bay of Bengal and 8 over the Arabian Sea. Arabian Sea remained exceptionally active in terms of cyclogenesis this year, especially in the post monsoon season. The season-wise distribution had been one cyclonic storm in winter, one in pre-monsoon season, 2 depressions and 2 very severe cyclonic storms during the monsoon season and 4 cyclonic storms and 3 depressions in Post monsoon season.